INFORMATION AND COMMUNICATION TECHNOLOGIES: RESEARCH ON THE CONTRIBUTIONS OF LEARNING OBJECTS IN THE PROCESS OF LITERACY - Daderio de Melo, Andressa Cristina [UNESP]; Camara Pereira, Ana Claudia [UNESP]; Fiscarelli, Silvio Henrique [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
In recent decades, Brazil has proposed and implemented a set of public policies in the field of education that propose actions aimed at improving the process of literacy, and establish goals aimed at improving the quality of education. The results obtained through the application of large-scale assessment tools show that one of Brazil's great challenges is to improve levels of proficiency in reading, writing and mathematics, since even after three years of schooling 22% of students only developed elementary skills. The use of technology as a playful, motivating element has proven to be an efficient resource capable of promoting the cognitive development of children. Thus, we have developed Learning Objects, as a resource to support the literacy process, in order to verify their their possible contributions through a systematic analysis of practices in 1st and 2nd grade classrooms.
Keywords: Public policies; Learning objects; Assessment